Presumed Fourth Nerve Palsy in a Healthy and Asymptomatic Child with COVID-19 Infection - kiarudi, Mohammad Yaser; sharifi, mohammad; Gharouni, Ahmad; Shiravi, Tayebe (Iranian Journal of Child Neurology, 2024)
COVID-19 can cause a wide range of ocular manifestations. The most common ocular manifestation is conjunctivitis. Neuro-ophthalmic presentations of COVID-19 are rare. Case reports suggest that COVID-19 infection can cause cranial nerve palsy, including nerves that regulate ocular movements. The present studypresented a case of fourth nerve palsy in a healthy and asymptomatic COVID-19-infected child. A healthy 10-year-old boy was referred to our eye clinic with a complaint of recent abnormal head posture and squint. His past medical history was unremarkable, and he had not received any medication or vaccinations within the last few weeks. No history of ocular or head trauma was observed. The patient was afebrile and had no respiratory symptoms. A comprehensive ocular examination was performed. All examinations, including slit-lamp, pupils, eyelids, and optic nerve heads, were normal. In ocular motor evaluations, left eye hyperdeviation was observed. Because of the history of COVID-19 in the mother of the child, he was referred to an infectious disease specialist and was tested for SARS-COV-2 with a nasopharyngeal swab specimen. The test was positive and SARS-COV-2 was detected. In addition, the patient was referred to a pediatric neurology department. Brain and orbital MRI was performed, and it was unremarkable. The post-viral fourth nerve palsy is uncommon, and post-COVID-19 has not been reported before. Clinicians should consider this infection in any recent strabismus in pediatrics. The children rarely complain of diplopia, and a recent abnormal head posture may be a sign of acquired strabismus.